Perceived Health Beliefs of Fertile Age Women Upon Early Breast Examination - Aida Rahmatari (Universitas Airlangga, 2014)
ABSTRACT Breast cancer remains a problem in Indonesia because 68.6% of patients see a doctor at an advanced stage, while in the early stages are only 22.4%. One of precaution can be done by early detection of breast cancer with breast examination. This study was conducted to analyze the relationship between perceived health beliefs of fertile age women with practice of early breast examination. This study is an observational analytic study using a case-control design. Samples were taken from the population by simple random sampling. Total sample are 24 case groups and 24 control groups. The independent variables were perceived threat, perceived benefits, perceived barriers. The dependent variables were practice of early breast examination. The results of the study were analyzed by using Chi Square test. The results of bivariat analyze are known that the variables are related to the practice of early breast examination are perceived threat (p = 0,013), and perceived barriers (p = 0,021). Variables that are not related to the practice of early breast examination are perceived benefit (p = 0,348). The conclusion is perceived threat, and perceived barriers in fertile age women are significantly related to practice of early breast examination. Advised for women to be able to be a savior for himself and the booster and motivator to the other women in the neighborhood for the early detection of breast cancer. Keywords: breast cancer, breast examination, early detection, fertile age                       woman, perceived